Body image in older, inpatient women and the relationship to BMI, anxiety, depression, and other sociodemographic factors. (2nd December 2019) - Dean, Elspeth; Haywood, Cilla; Hunter, Peter; Austin, Nicole; Prendergast, Luke
Abstract : Objectives: To determine the prevalence of body image dysfunction in a cohort of older, inpatient women, and to examine any associated health or sociodemographic factors. Methods: In this cross‐sectional, observational study, 50 older women admitted to a subacute hospital completed the Body Shape Questionnaire (BSQ‐34), Geriatric Depression Screen (GDS), and Geriatric Anxiety Index (GAI). Additional sociodemographic and health‐related data including body mass index (BMI) were collected on all participants. Data were first analysed to determine the prevalence of body image dysfunction. To examine factors significantly associated with body image impairment, partial correlation analyses were initially performed between BSQ‐34 score and included variables, followed by stepwise regression analysis undertaken to determine significantly contributing independent variables. Results: Only three out of 50 women displayed body image dysfunction using suggested cut‐off scores from the BSQ‐34, giving a prevalence rate of only 6%. After controlling for multiple variables however, both higher GDS score and higher BMI were found to be significantly and independently associated with poorer body image, with the strongest association being between higher BSQ‐34 score and higher BMI (Spearman rank r = 0.455, P < 0.001). Furthermore, when high BMI and depression occurred together, this association was even greater, accounting for over 50% of the impact on body image scores ( P = 0.0001). Conclusion: For this small cohort of older, inpatient women, rates of body image dysfunction were low. There did however appear to be an association between poorer body image and higher BMI and depression rates in the group, which may be worth exploring further in less frail, community‐dwelling cohorts.